Radio Frequency Interference Measurements for a Radio Astronomy Observatory Site in Indonesia - Peberlin Parulian Sitompul; Timbul Manik; Mario Batubara; Bambang Suhandi (Aerospace, 2021)
We report on the measurements of radio frequency interference (RFI) at Mount Timau, Kupang, Indonesia, which is intended to host a future radio astronomy observatory. These measurements were taken twice in October 2020 and December 2020 to obtain the RFI environment, at frequencies between 70 and 7000 MHz. Due to the limitations of the measurement data, the results presented in this paper are based on peak detection rather than statistical analysis. Based on the measurement results, the frequency interval between 70–88 MHz and 120–150 MHz is relatively quiet, and the frequency range of 150–300 MHz is relatively clear. The frequency interval of 300 to 800 MHz is relatively quiet, except at the frequency of 600 MHz. The frequency range of 800–1400 MHz is also relatively quiet. The predominant terrestrial services in this band are at 840 MHz, with an amplitude around 32 dB, and 916 MHz, with an amplitude around 12 dB, and the global system for mobile (GSM) signals around 954 MHz have an amplitude around 20 dB above the noise floor. The frequency range of 1400–7000 MHz is also relatively quiet. In this band frequency, we can see RFI at 2145 and 2407 MHz, emitted by local Wi-Fi, and at 2683 MHz, with amplitudes of 18, 40 and 15 dB, respectively, from the noise level. We conclude that, for this period, the frequency band allocated for astronomy can possibly be used for radio telescope development.